Cervical cancer screening intervals and management for women living with HIV: a risk benchmarking approach. (24th April 2017) - Robbins, Hilary A.; Strickler, Howard D.; Massad, L. Stewart; Pierce, Christopher B.; Darragh, Teresa M.; Minkoff, Howard; Keller, Marla J.; Fischl, Margaret; Palefsky, Joel; Flowers, Lisa; Rahangdale, Lisa; Milam, Joel; et al.
Abstract : Objective: We suggested cervical cancer screening strategies for women living with HIV (WLHIV) by comparing their precancer risks to general population women, and then compared our suggestions with current Centers for Disease Control and Prevention (CDC) guidelines. Design: We compared risks of biopsy-confirmed cervical high-grade squamous intraepithelial neoplasia or worse (b HSIL+), calculated among WLHIV in the Women's Interagency HIV Study, to 'risk benchmarks' for specific management strategies in the general population. Methods: We applied parametric survival models among 2423 WLHIV with negative or atypical squamous cell of undetermined significance (ASC-US) cytology during 2000–2015. Separately, we synthesized published general populationb HSIL+ risks to generate 3-year risk benchmarks for a 3-year return (after negative cytology, i.e. 'rescreening threshold'), a 6–12-month return (after ASC-US), and immediate colposcopy [after low-grade squamous intraepithelial lesion (LSIL)]. Results: Average 3-yearb HSIL+ risks among general population women ('risk benchmarks') were 0.69% for a 3-year return (after negative cytology), 8.8% for a 6–12-month return (after ASC-US), and 14.4% for colposcopy (after LSIL). Most CDC guidelines for WLHIV were supported by comparing risks in WLHIV to these benchmarks, including a 3-year return with CD4 + greater than 500 cells/μl and after either three negative cytology tests or a negative cytology/oncogenic human papillomavirus cotest (all 3-year risks⩽1.3%); a 1-year return after negative cytology with either positive oncogenic human papillomavirus cotest (1-year risk = 1.0%) or CD4 + cell count less than 500 cells/μl (1-year risk = 1.1%); and a 6–12-month return after ASC-US (3-year risk = 8.2% if CD4 + cell count at least 500 cells/μl; 10.4% if CD4 + cell count = 350–499 cells/μl). Other suggestions differed modestly from current guidelines, including colposcopy (vs. 6–12 month return) for WLHIV with ASC-US and CD4 + cell count less than 350 cells/μl (3-year risk = 16.4%) and a lengthened 2-year (vs. 1-year) interval after negative cytology with CD4 + cell count at least 500 cells/μl (2-year risk = 0.98%). Conclusions: Current cervical cancer screening guidelines for WLHIV are largely appropriate. CD4 + cell count may inform risk-tailored strategies. Abstract : Supplemental Digital Content is available in the text